Single-molecule imaging of UvrA and UvrB recruitment to DNA lesions in living Escherichia coli - Mathew Stracy; Marcin Jaciuk; Stephan Uphoff; Achillefs N. Kapanidis; Marcin Nowotny; David J. Sherratt; Pawel Zawadzki (Nature Communications, 2016)
Nucleotide excision repair is able to identify and remove a wide range of DNA helix distorting lesions from the genome. Here the authors use single molecule imaging of UvrA and UvrB molecules and suggest a two-step ‘scan and recruit’ model for UvrA function.